ChemInform Abstract: First‐Principles Calculation of NMR Parameters Using the Gauge Including Projector Augmented Wave Method: A Chemist′s Point of View. Issue 8 (1st March 2013) - Bonhomme, Christian; Gervais, Christel; Babonneau, Florence; Coelho, Cristina; Pourpoint, Frederique; Azais, Thierry; Ashbrook, Sharon E.; Griffin, John M.; Yates, Jonathan R.; Mauri, Francesco; et al., et al.
Abstract Review: 439 refs.